Ч. 2; Английский язык: пособие для студентов технических вузов - Диденко А. В. Анастасия Владимировна; Надеина Л. В. Луиза Васильевна; Степура С. Н. Светлана Николаевна; Уткина А. Н. Анна Николаевна; Федоринова З. В. Зоя Владимировна; Чеснокова И. А. Ирина Анатольевна (2022, 2022)
Заглавие с титульного экрана